93 AUTISM SPECTRUM DISORDERS IN BOYS WITH THE FRAGILE X PREMUTATION. (1st January 2005) - Farzin, F.; Perry, H.; Hessl, D.; Loesch, D. Z.; Cohen, J.; Gane, L. W.; Kradin, M.; Hagerman, R. J.
Abstract : Purpose: It is commonly believed that individuals with the premutation allele (55 to 200 CGG repeats) of the fragile X mental retardation 1 (FMR1) gene are clinically unaffected compared to those with full mutation alleles (≥200 repeats). This study reports on 15 probands, the first affected individual to present clinically and 12 nonprobands identified through pedigree analysis. We compare both premutation groups to 17 male siblings without the FMR1 mutation. Understanding the variability among individuals with the fragile X premutation is important in early identification of symptoms, proper diagnosis, and therapeutic intervention. Methods: This preliminary study includes 27 males with the FMR1 premutation, ranging in age from 5 to 22 years (mean age=10). Fifteen of them are probands and 12 are nonprobands. Seventeen male siblings without the FMR1 mutation, ages 5 to 22 (mean age=10), were included as controls. Parents of child participants completed the Conners' Global Index-Parent Version (CGI) and the Social Communication Questionnaire (SCQ. For a number we have Full Scale IQ scores. In addition, parents reported on learning disabilities, social deficits, and therapies and medications used in treatment. Summary: Mean SCQ and CGI scores of probands and nonprobands combined were significantly different (p≤0.05) compared to controls. Results show 94% of probands, 42% of nonprobands, and 18% of controls met criteria for ADHD as demonstrated by a score of 15 or greater on the CGI and based on DSM-IV criteria. Symptoms of ASD were confirmed by a score of 15 or greater on SCQ in 59% of probands, 17% of nonprobands, and none of controls. By DSM-IV criteria, 73% of probands, 17% of nonprobands, and none of controls are on the autism spectrum. 40% of probands and 17% of nonprobands had full autism and 33% of probands had PDDNOS, which is significantly different from our control population. Based on parent report, 87% of probands, 70% of nonprobands, and none of controls demonstrated poor eye contact. Conclusion: Our results show that the majority of young boys who present with the premutation as well as those that do not present have autism spectrum disorders and ADHD. In addition, cognitive deficits and other behavior problems, including anxiety and poor eye contact are common. Therefore, it is important for clinicians to carry out DNA testing on all siblings of individuals identified with fragile X syndrome so children with the premutation can be identified, evaluated, and treated for these problems.